Ascaris suum in pigs of the Zona da Mata, Minas Gerais State, Brazil - Fausto, Mariana Costa; Oliveira, Isabela de Castro; Fausto, Guilherme Costa; Carvalho, Lorendane Millena de; Valente, Fabrício Luciani; Campos, Artur Kanadani; Araújo, Jackson Victor de (Revista Brasileira de Parasitologia Veterinária, 2015)
Among the parasites that affect pigs, Ascaris suum stands out for causing the greatest losses to livestock production systems. This parasite can be monitored during the slaughter of animals through the identification of “milk spots” or white patches on the liver caused by its larval migration. However, infection in the herd is usually subclinical, which is why the presence of this parasite in industrial pig production has been overlooked. The aim of the study was therefore to evaluate the occurrence of milk spots on the liver of animals slaughtered in the micro-region of Ponte Nova in the Zona da Mata - Minas Gerais, Brazil, and to associate these lesions with the time of year, herd size and source of origin of the animals. An evaluation was made of 1,069 lots, totaling 108,073 animals, based on data extracted from the Federal Inspection Service. The animals were slaughtered during the period of January 2011 to June 2013. Out of the total number of slaughtered animals, 10,535 (9.75%) tested positive for these lesions. Therefore, veterinarians and producers should be warned about the inefficiency of the deworming protocols that are used, and the need to develop and/or review control strategies for this parasite in production systems.

Dentre os parasitas que acometem os suínos, Ascaris suumdestaca-se como o mais impactante nos sistemas de criação. Seu monitoramento pode ser realizado durante o abate dos animais, por meio da identificação de “milk spots” ou manchas de leite presentes no fígado, decorrentes da sua migração larval. Entretanto devido ao fato da infecção ocorrer no rebanho normalmente de forma subclínica, a presença desse parasita na produção industrial de suínos vem sendo negligenciada. O objetivo do estudo foi avaliar a ocorrência de manchas de leite no fígado de animais abatidos na micro-região de Ponte Nova, na Zona da Mata de Minas Gerais - Brasil, e associar tais lesões com a época do ano, tamanho do rebanho e local de origem dos animais. Foram avaliados 1.069 lotes, totalizando 108.073 animais. Os dados foram extraídos do Serviço de Inspeção Federal, e eram referentes aos animais abatidos, durante o período de janeiro de 2011 a junho de 2013. Do total de animais abatidos, 10.535 (9,75%) foram positivos para a lesão. Portanto, veterinários e produtores devem ser alertados quanto à ineficiência dos protocolos de vermifugação utilizados e a necessidade do desenvolvimento e/ou revisão de estratégias de controle para este parasita na produção.
Keywords: Ascaris suum; Control; Liver; Nematodes; Deworming; Pigs